Posture, Balance and the Brain 2015
DOI: 10.11610/posture.07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Transcutaneous Vagal Stimulation on the EEG Power Maps, EEG Sources Distribution and Steadiness of Quiet and Sensory-conflicted Stance

Abstract: Transcutaneous vagal stimulation (t-VNS) is a prospective method as a cheap and noninvasive alternative of surgical cervical vagal stimulation widely used for treatment of refractory epilepsy, depression etc. Data on its application in healthy people are scarce. A lot of problems concerning the acting mechanisms and cortical representation are unsolved. We did acute t-VNS and studied the standing balance steadiness, EEG absolute power maps and sources distribution. We found improvement of the steadiness of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Implanted VNS in epilepsy patients have mostly failed to demonstrate an impact of VNS on the background EEG, even when looking at the effects of chronic intermittent stimulation (73)(74)(75). However, studies using brief transcutaneous auricular stimulation have demonstrated acute EEG effects consistent with those observed here (76). The failures in epilepsy patients may reflect already compromised noradrenergic, serotonergic, and GABAergic neurotransmitter systems that can no longer be easily modulated by peripheral nerve stimulation.…”
Section: Wwwneuromodulationjournalcomsupporting
confidence: 61%
See 1 more Smart Citation
“…Implanted VNS in epilepsy patients have mostly failed to demonstrate an impact of VNS on the background EEG, even when looking at the effects of chronic intermittent stimulation (73)(74)(75). However, studies using brief transcutaneous auricular stimulation have demonstrated acute EEG effects consistent with those observed here (76). The failures in epilepsy patients may reflect already compromised noradrenergic, serotonergic, and GABAergic neurotransmitter systems that can no longer be easily modulated by peripheral nerve stimulation.…”
Section: Wwwneuromodulationjournalcomsupporting
confidence: 61%
“…Another major projection of NST is to the dorsal raphe nucleus (DRN), so it is expected that nVNS should also modulate serotonergic activity . The slope of the loudness dependent auditory evoked response as studied here is widely accepted as an inverse measure of central serotonergic activity, as supported by both human and animal studies , although there have been a few pharmacological studies that do not support LDAER as a good index of acute serotonergic tone .…”
Section: Discussionmentioning
confidence: 99%
“…First, we do not have a direct measurement of vagus nerve activity. A number of studies utilizing the same cervical nVNS device have found neural evidence supporting stimulation of the vagus with similar stimulation-specific sensory evoked potentials as implantable devices [ 39 , 99 , 100 ] and changes in power spectrum consistent with inhibitory electrical activity [ 35 , 101 ]. Regarding the sham device, participants were not asked what type of stimulation they received.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those authors also found increased activation in the insula, precentral gyrus and the thalamus (Kraus et al, 2007). Using electroencephalogram (EEG) signals, Dimitrov and Gatev (2015) implicated taVNS with brain activation at the superior temporal gyrus, middle temporal gyrus, precuneus, cuneus and left inferior parietal lobule; whereby EEG was used as a proxy to reconstruct the source localized at these functional structures, via lowresolution brain electromagnetic tomography (LORETA). Heightened motion sickness induces atypical brain activity.…”
Section: Introductionmentioning
confidence: 99%